Ultrasensitive Optical Detection of Water Pressure in Microfluidics Using Smart Reduced Graphene Oxide Glass - Xin, Wei; Wu, Tiange; Zou, Tingting; Wang, Ye; Jiang, Wenshuai; Xing, Fei; Yang, JianJun; Guo, Chunlei (Frontiers in Chemistry, 2019)
Despite recent progresses in the field of microfluidics, the effect of liquid pressure on the detection accuracy has been rarely studied. Here, we perform a quantitative analysis of such effect, by utilizing the sensitive optical responses of graphene to the refractive index (RI) change of its surrounding environment. We utilize a reflection coupling configuration by combining the total internal reflection (TIR) and ultrasonic waves. The high-performance graphene is processed on common glasses by using the solution-processable oxidation-reduction method. We find that the RI change of water caused by a pressure as small as 500 Pa generated by the liquid level change in the microfluidics can be measured directly. The detection accuracy and response time limits are approximately 280 Pa and 100 ns, respectively. The Maxwell’s boundary conditions, Fresnel's law, and Pascal's law are used in theoretical analyses. This work highlights the importance of liquid pressure in microfluidics and provides guidance in designing and accurate detection of microfluidic devices.